2020
DOI: 10.1016/j.psj.2019.10.004
|View full text |Cite
|
Sign up to set email alerts
|

Effects of star anise (Illicium verum Hook.f) oil on the nuclear factor E2–related factor 2 signaling pathway of chickens during subclinical Escherichia coli challenge

Abstract: We characterized the mechanism underlying star anise ( Illicium verum Hook.f) oil ( SAO )–mediated antioxidant status during subclinical Escherichia coli ( E. coli ) challenge. A total of 512 male birds (White Leghorn) at 30 wk of age with similar body weight (2.14 ± 0.02 kg) were randomly divided into 2 groups with 1 group being orally challenged with E. coli (every other day from day 15 to d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9
1

Relationship

3
7

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 25 publications
0
5
0
Order By: Relevance
“…Upon activation, Nrf2 moves into cell nucleus after releasing from Keap 1, where it is combined to the antioxidant response element to activate transcription of antioxidant genes. Similarly, it has been demonstrated that star anise oil could reduce the oxidative stress of birds during subclinical Escherichia coli challenges through upregulation of the Nrf2 signaling pathway ( 47 ). In addition, we found that NE infection resulted in vacuolization and swelling in the mitochondria, while TA administration improved that.…”
Section: Discussionmentioning
confidence: 99%
“…Upon activation, Nrf2 moves into cell nucleus after releasing from Keap 1, where it is combined to the antioxidant response element to activate transcription of antioxidant genes. Similarly, it has been demonstrated that star anise oil could reduce the oxidative stress of birds during subclinical Escherichia coli challenges through upregulation of the Nrf2 signaling pathway ( 47 ). In addition, we found that NE infection resulted in vacuolization and swelling in the mitochondria, while TA administration improved that.…”
Section: Discussionmentioning
confidence: 99%
“…The main functions of IVE are anti-bacterial, enhancing the body's antioxidant and immune functions [17,18]. Studies have shown that IVE can exert its antibacterial function by inhibiting the formation of biofilm and reducing bacterial adhesion [19].…”
Section: Introductionmentioning
confidence: 99%
“…Our previous study revealed that high level of TA (800 mg/kg) had an inferior effect on nutrient digestibility and intestinal barrier function ( Yu et al, 2021 ). Ding et al (2020) also demonstrated that SAO improved the growth performance antioxidant status of broilers in a dose-dependent manner. As mentioned earlier, TA, which is faint yellow with a highly anise flavor, may be responsible for the bioactivities of SAO.…”
Section: Discussionmentioning
confidence: 77%